2013
DOI: 10.1093/humrep/des471
|View full text |Cite
|
Sign up to set email alerts
|

The sperm protamine mRNA ratio as a clinical parameter to estimate the fertilizing potential of men taking part in an ART programme

Abstract: None.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 37 publications
4
42
0
Order By: Relevance
“…Indeed, 87% of patients with abnormally high P1/P2 ratios exhibited P2 under-expression, while only a small proportion of patients with high P1/P2 exhibited P1 over-expression (13%) (Aoki et al, 2005a). Moreover, in the subfertile patients, highly aberrant protamine ratio was much more common than lowly aberrant protamine ratio, with the ratio of 2.92 (108/37) (Aoki et al, 2005a), 1.86 (26/14) (Aoki et al, 2006a), and5.91 (65/11) (de Mateo et al, 2009) reported by three of the studies included in our review, which was consistent with the results of own cohort studies (Rogenhofer et al, 2013). Therefore, in this meta-analysis, the overall protamine ratio in the infertile patients was much higher than in the controls, although there was a small part of patients with low protamine ratios.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Indeed, 87% of patients with abnormally high P1/P2 ratios exhibited P2 under-expression, while only a small proportion of patients with high P1/P2 exhibited P1 over-expression (13%) (Aoki et al, 2005a). Moreover, in the subfertile patients, highly aberrant protamine ratio was much more common than lowly aberrant protamine ratio, with the ratio of 2.92 (108/37) (Aoki et al, 2005a), 1.86 (26/14) (Aoki et al, 2006a), and5.91 (65/11) (de Mateo et al, 2009) reported by three of the studies included in our review, which was consistent with the results of own cohort studies (Rogenhofer et al, 2013). Therefore, in this meta-analysis, the overall protamine ratio in the infertile patients was much higher than in the controls, although there was a small part of patients with low protamine ratios.…”
Section: Discussionsupporting
confidence: 90%
“…As the raw data in one article were extracted from a multicenter study (Rogenhofer et al, 2013), the results of protamine-mRNA ratios of the different study centers were analyzed in this systematic review in order to prevent measurement bias. We subanalyzed the data with regard to the different types of assays used to Figure 3 Funnel plot of the included studies used to evaluate the correlation coefficient (COR) between protamine deficiency and sperm DNA damage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations